2020
DOI: 10.1080/02602938.2020.1790500
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes high quality higher education pedagogical research?

Abstract: Over the last 20 years there has been significant growth in the volume of higher education pedagogical research across disciplines and national contexts, but inherent tensions in defining quality remain. In this paper we present a framework to support understanding of what constitutes internationally excellent research, drawing on a range of conceptual frameworks, international and national performance-based research funding systems, discipline/professional body frameworks, and research council guidance. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 55 publications
2
16
1
1
Order By: Relevance
“…Such efforts seem to increase parity of teaching and research, imposing challenges to developing shared understandings of pedagogic research and building pedagogic research communities. Although Evans et al (2020) propose the concept of "integrated academic," suggesting interdisciplinary communities of practice across research and pedagogical teams be promoted, our findings show that teaching-focused, public serviceoriented academics who occupy the bottom of the academic hierarchy have neither access to interdisciplinary research networks nor legitimacy to construct a pedagogic research community.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Such efforts seem to increase parity of teaching and research, imposing challenges to developing shared understandings of pedagogic research and building pedagogic research communities. Although Evans et al (2020) propose the concept of "integrated academic," suggesting interdisciplinary communities of practice across research and pedagogical teams be promoted, our findings show that teaching-focused, public serviceoriented academics who occupy the bottom of the academic hierarchy have neither access to interdisciplinary research networks nor legitimacy to construct a pedagogic research community.…”
Section: Discussioncontrasting
confidence: 68%
“…The findings add to the recent discussions about the position and quality of pedagogic research in HE (Cotton et al, 2018;Evans et al, 2020;Tierney, 2020). The study indicates the perception of pedagogic research as being of lower value is prevalently embedded in institutional structure (Cotton et al, 2018), in which academics perceive research and teaching as competing rather than complementary.…”
Section: Discussionsupporting
confidence: 62%
“…However, it should be noted that only one institute at a single university was invited to take part in the research, so it is possible that the results might provide answers that can be mapped to disciplinary bias (Bantanur et al , 2015b). However, in designing, implementing and reporting this study, key features of the pragmatic pedagogic research framework development by Evans et al (2021) were reflected upon. Using this, the researchers were able to consider the factors such as the pedagogical clarity of the study, methodological transparency and methodological congruence, which are identified by Evans et al (2021) as underpinning high-quality pedagogic research.…”
Section: Methodsmentioning
confidence: 99%
“…Da sie aber -jenseits von DBR -von rivalisierenden Forschungsansätzen unterschiedlich gewichtet und bewertet werden, lässt sich die meist implizite Vorstellung eines inversen Verhältnisses schwer ausräumen, das dem Motto folgt: je mehr Rigor, desto weniger Relevanz beziehungsweise je mehr Relevanz, desto weniger Rigor. Einer solchen Vorstellung wird erwartungsgemäß vor allem in DBR, aber auch in der Bildungsforschung generell und darüber hinaus mit verschiedenen Argumenten durchaus widersprochen: Man könne Rigor und Relevanz ausbalancieren (Reeves, 2011;Evans et al, 2021); Relevanz sei auch eine Eigenschaft von Wissenschaftlichkeit (Dilger, 2012); Relevanz für die Praxis müsse zu einem Schlüsselkriterium für Rigor werden (Gutiérrez & Penuel, 2014, p. 22); man brauche Rigor bei der Anwendung von allen (auch für Relevanz ausgelegten) Standards (Prochner & Godin, 2022, p.…”
Section: Standards Auf Der Ebene Der Designangemessenheitunclassified